2018
DOI: 10.17977/um017v23i22018p085
|View full text |Cite
|
Sign up to set email alerts
|

Pendidikan Kesiapsiagaan Bencana Tanah Longsor Untuk Siswa Anak Usia Dini Dengan Metode Dongeng Berbasis Media Pop Up Book Di Paud Dewi Sartika Kecamatan Bergas

Abstract: This study aims to design and compose a fairy tale script about landslide disaster preparedness, design and make pop up book about landslide disaster preparedness, and to know effectiveness of storytelling method with Pop Up Book media in education of landslide disaster preparedness. The research method used is experimental method. Sampling is done by purposive sampling technique in low class, while data collection in this research through observation, interview and questionnaire. The analysis technique used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…Therefore, pop-up book media in mathematics learning is more effective when compared to learning by lecturing or without using media (Anies & Mariana (2018). Benardi (2017) revealed that the average activity of students during the following mediaassisted learning pop-up book is high and is improvement in all response indicators students towards learning more reinforce that the media pop-up book effectively used in learning PAUD students.…”
Section: Comparison Of Educational Media With Video and Pop-up Book Towards Knowledge Of Balanced Nutrition Guidelinesmentioning
confidence: 78%
“…Therefore, pop-up book media in mathematics learning is more effective when compared to learning by lecturing or without using media (Anies & Mariana (2018). Benardi (2017) revealed that the average activity of students during the following mediaassisted learning pop-up book is high and is improvement in all response indicators students towards learning more reinforce that the media pop-up book effectively used in learning PAUD students.…”
Section: Comparison Of Educational Media With Video and Pop-up Book Towards Knowledge Of Balanced Nutrition Guidelinesmentioning
confidence: 78%
“…This is similar to the finding of [9], which this method should be able to add the emotional experience and in-depth understanding for students. One of the article that studied stated that the storytelling method combined with pop-up book media was used to teach a topic about landslide disaster mitigation to preschool students, and the result was that students become more interested in learning so it was easier to understand the process of disasters and the mitigation actions [39].…”
Section: Discussionmentioning
confidence: 99%
“…Explanation of phenomena in quantitative data can be analyzed based on the result by percentage like Sukariasih, Purwana, Nursalam, Sahara, and Reskiawan (2019) research. Anccording to Benardi (2018) the young have high potention to participate and increase they knowledge about disaster.According to Sari (2019) the eldery age classification get the big percentage as victim in the Mount Merapi eruption, so can indicate that the eldery not have time and energy to participated in the disaster sosialization programe.…”
Section: Discussionmentioning
confidence: 99%